Interactions of combined bile acids on hepatocyte viability: cytoprotection or synergism - Rolo, Anabela P. (2002)
Cholestasis results from hepatocyte dysfunction due to the accumulation of bile acids in the cell, many of which are known to be cytotoxic. Recent evidence implicates competitive antagonism of key cytotoxic responses as the mechanism by which certain therapeutic bile acids might afford cytoprotection against cholestasis. In this work, we compare the relative cytotoxicity of bile acids in terms of dose- and time-dependence. To better elucidate the controversy related to the therapeutic use of ursodeoxycholate (UDCA) in cholestatic patients, we also evaluated the effects of bile acid combinations. Viability of Wistar rat hepatocytes in primary culture was measured by LDH leakage after 12 and 24 h exposure of cells to the various bile acids. All unconjugated bile acids caused a dose-dependent decrease in cell viability. The tauro- and glyco-conjugates of chenodeoxycholate (CDCA) and UDCA were all less toxic than the corresponding unconjugated form. Although relatively non-toxic, UDCA caused synergistic cell killing by lithocholate (LCA), CDCA, glyco-CDCA (GCDC) and tauro-CDCA (TCDC). Glycoursodeoxycholate decreased the toxicity of GCDC, but potentiated the toxicity of unconjugated CDCA and LCA. The tauro-conjugate of UDCA had no significant effect. These data suggest that at cholestatic concentrations, bile acid-induced cell death correlates with the degree of lipophilicity of individual bile acids. However, these results indicate that the reported improvement of biochemical parameters in cholestatic patients treated with UDCA is not due to a direct effect of UDCA on hepatocyte viability. Therefore, any therapeutic effect of UDCA must be secondary to some other process, such as altered membrane transport or nonparenchymal cell function.